Do PGY-1 residents in Emergency Medicine have enough experiences in resuscitations and other clinical procedures to meet the requirements of a Competence by Design curriculum? - Crickmer, Michael; Lam, Tobi; Tavares, Walter; Meshkat, Nazanin (Canadian Medical Education Journal, 2021)
Background: With the transition to a Competence by Design (CBD) curriculum, Fellow of the Royal College of Physicians in Emergency Medicine (FRCP-EM) training has created guidelines on experiences residents should have before progressing. We sought to quantify adult medical resuscitations and clinical procedures completed by PGY1 FRCP-EM residents to compare them to CBD requirements with the aim to identify areas of limited exposure requiring curriculum revisions prior to nation-wide CBD implementation. Methods: Twenty-two PGY1 residents from four FRCP-EM programs recorded their activities from July 2017 to June 2018 in an online log that tracked resuscitations and procedures along with role assumed, supervision, and level of comfort. Results: In total 515 resuscitations were logged with the median number per resident 15 (range 0 to 98). The most frequent resuscitation was altered mental status and the least was unstable dysrhythmia. 557 total procedures were logged with the median number 75 (range 8 to 273). The most frequent procedure done was simple laceration repair and the least frequent was intraosseous access. Conclusions: Unstable dysrhythmias and cardiorespiratory arrest along with intraosseous access and arthrocentesis are low event clinical exposures. In the era of CBD, the misalignment of entrustrable professional activity (EPA) targets and curriculum delivery should be monitored/reviewed to ensure expectations are realistic and that sufficient exposures are available.